Mechanism of the formation and properties of antimony polyphosphate - Melnikov, P.; Dos Santos, F. J. [UNESP]; Santagnelli, S. B. [UNESP]; Secco, M. A C; Guimarães, W. R.; Delben, A.; Delben, J. R. (Springer Nature, 2005)
Formation of antimony polyphosphate using Sb2O3 and/or (NH4)2HPO4 and NH4H 2PO4 as starting materials has been simulated by thermal analysis technique. The elimination of water and ammonia molecules induced by heating leads to the formation of intermediate ammonium polyphosphate, which subsequently reacts with Sb2O3. Morphologically, vitreous Sb(PO3)3 is composed of plaques having irregular shapes. Infrared spectra and NMR study is consistent with tetrametaphosphate anion arrangement. The compound is thermally unstable and may be recommended as a donor of -O-P-O- linkers in the preparation of special phosphate glasses. © 2005 Akadémiai Kiadó, Budapest.
Keywords: Antimony; Glasses; Inorganic materials; Polyphosphate; Crystallization; Differential thermal analysis; Heating; Infrared spectroscopy; Materials science; Metallic glass; Morphology; Nuclear magnetic resonance; Phosphates; Reaction kinetics; Ammonia molecules; Phosphate glasses; Antimony compounds